The Relationship of Higher Education Access with Final Marks in a Core Chemical Engineering Topic - Sena-Esteves, Maria Teresa (2021)
This present work cracks to understand the relationship between final marks in a topic with competences that are core of Chemical Engineering and students’ access grades to a Portuguese Higher Education Institution (HEI). The study is based on data gathered through a questionnaire concerning students’ perceptions about assessment and teaching-learning methodologies in four academic years (2016-2017 to 2019-2020). The student´s access grades were included in the questionnaire since 2018-19 academic year allowing to establish a relationship with the final marks obtained in a core Chemical Engineering Topic, Fluid Mechanics. From the analysis made, it can be said that students who obtained higher access grades to HEI may have also a higher Chemical Engineering curricular unit final mark, although the low linear relationship obtained (r =0.45) for the year 2019-20.